MiR-140 targeting CTSB signaling suppresses the mesenchymal transition and enhances temozolomide cytotoxicity in glioblastoma multiforme. (September 2019) - Ho, Kuo-Hao; Cheng, Chia-Hsiung; Chou, Chih-Ming; Chen, Peng-Hsu; Liu, Ann-Jeng; Lin, Cheng-Wei; Shih, Chwen-Ming; Chen, Ku-Chung
Graphical abstract: Abstract: Temozolomide (TMZ) is a first-line chemotherapeutic agent used against glioblastoma multiforme (GBM), but this disease exhibits recurrence and high lethality. Therefore, it is critical to explore biomarkers which involve in drug resistance and can be represented as different therapeutic effects after a diagnosis. We attempted to investigate the underlying variably expressed genes that contribute to the formation of resistance to TMZ. We analyzed gene and microRNA (miR) data from GBM patients in The Cancer Genome Atlas (TCGA) database to identify genetic factors associated with poor TMZ efficacy. By conducting a gene set enrichment analysis (GSEA), the epithelial-to-mesenchymal transition (EMT) was associated with poor TMZ responses. To identify roles of microRNAs in regulating TMZ resistance, a differential microRNA analysis was performed in TMZ-treated GBM patients. Downregulation of miR-140 was significantly correlated with poor survival. By integrating TCGA transcriptomic data and genomics of drug sensitivity in cancer (GDSC), cathepsin B (CTSB) was inversely associated with miR-140 expression and poor TMZ efficacy. By a pan-cancer analysis, both miR-140 and CTSB were found to be prognostic factors in other cancer types. We also identified that CTSB was a direct target gene of miR-140. Overexpression of miR-140 reduced CTSB levels, enhanced TMZ cytotoxicity, suppressed the mesenchymal transition, and influenced CTSB-regulated tumor sphere formation and stemness marker expression. In contrast, overexpression of CTSB decreased TMZ-induced glioma cell death, promoted the mesenchymal transition, and attenuated miR-140-increased TMZ cytotoxicity. These findings provide novel targets to increase the therapeutic efficacy of TMZ against GBM.